THE EFFECT OF MARKETING COMMUNICATION AND RELIGIOCITY ON CUSTOMER LOYALTY: CASE STUDY IN DOJO 37 - Hendratmoko; Mutiarawati, Elisabeth Vita (Lembaga Penelitian dan Pengabdian kepada Masyarakat Institut Bisnis dan Informatika Kwik Kian Gie, 2022)
The purpose of this study is to analyze the influence of marketing communication variables and religiocity variables on customer loyalty. This study also analyzed the role of religiocity variables as mediator variables between marketing communication variables and loyalty variables.This research uses a quantitative approach. and interviews with five respondents to confirm quantitative research findings. Sampling was conducted in February 2022. The population in this study was the entire Karateka Dojo 37 Indonesia in Rawamangun, East Jakarta. The number of samples in this research was 75 respondents. This number of samples meets the conditions in the analysis using the SEM-PLS method.The results of this study prove that marketing communication has a positive and significant influence on customer loyalty. Meanwhile religiocity has no influence on customer loyalty. The results of interviews with five respondents revealed that the improper way of delivery led to a multi-interpretation of the religiocity aspect. The religiocity variable cannot act as a mediator variable between marketing communication and loyalty.This research contributed to the theory of customer retaining strategies, especially in karate organizations in Indonesia. This research also proves that in today's era of very fierce competition, the use of marketing communication is one of the most effective ways to maintain customer loyalty.